1999
DOI: 10.1080/01635589909514744
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis in human breast cancer cells by tocopherols and tocotrienols

Abstract: The apoptosis-inducing properties of RRR-alpha-, beta-, gamma-, and delta-tocopherols, alpha-, gamma-, and delta-tocotrienols, RRR-alpha-tocopheryl acetate (vitamin E acetate), and RRR-alpha-tocopheryl succinate (vitamin E succinate) were investigated in estrogen-responsive MCF7 and estrogen-nonresponsive MDA-MB-435 human breast cancer cell lines in culture. Apoptosis was characterized by two criteria: 1) morphology of 4,6-diamidino-2-phenylindole-stained cells and oligonucleosomal DNA laddering. Vitamin E suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
113
1
4

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(130 citation statements)
references
References 28 publications
10
113
1
4
Order By: Relevance
“…More recent work has demonstrated that cell cycle inhibition by T3 occurs through the control of the Rb/cdk4/ cyclin D pathway (Elangovan et al 2008) that is also affected by the HM forms of tocopherols, and particularly by c-TOH (Betti et al 2006). In the same cell models, T3 were demonstrated to induce apoptosis with d-T3 as the most potent form (Yu et al 1999) and with a mechanism that involves mitochondrial disruption and cyt c release (Takahashi and Loo 2004). As introduced above, recent studies by our group confirmed that d-T3 is the most potent T3 form with pro-apoptotic activity higher than a-TOS in breast cancer cells (Table 1) .…”
Section: Metabolite Formation and Activitymentioning
confidence: 70%
“…More recent work has demonstrated that cell cycle inhibition by T3 occurs through the control of the Rb/cdk4/ cyclin D pathway (Elangovan et al 2008) that is also affected by the HM forms of tocopherols, and particularly by c-TOH (Betti et al 2006). In the same cell models, T3 were demonstrated to induce apoptosis with d-T3 as the most potent form (Yu et al 1999) and with a mechanism that involves mitochondrial disruption and cyt c release (Takahashi and Loo 2004). As introduced above, recent studies by our group confirmed that d-T3 is the most potent T3 form with pro-apoptotic activity higher than a-TOS in breast cancer cells (Table 1) .…”
Section: Metabolite Formation and Activitymentioning
confidence: 70%
“…However, polyunsaturated forms of VE may exert proapoptotic activity even with the redox-active hydroxyl group present. This is the case of g-T3H, which, unlike a-T3H, causes apoptosis in a variety of malignant cells (Yu et al, 1999;this report). An even stronger proapoptotic effect was observed for g-T2H, a homologue of g-T3H with the phenyl chain shorter by one isoprenyl unit.…”
Section: Resultsmentioning
confidence: 88%
“…Its desaturation, in the case of a-TOH, gives the naturally occurring a-T3H, which is nonapoptotic (Yu et al, 1999). g-T3H, however, has a strong apoptogenic activity (Yu et al, 1999), which is further enhanced by its conversion to g-T3S (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to tocopherols, the antiproliferative effects of tocotrienols are mediated by inhibition of protein kinase C [44]. In human and murine tumor cells, tocotrienols induce a cell-cycle arrest in the G-1 phase and apoptosis [54]. To the best of our knowledge, the potential of tocotrienols as antifibrotic agents has not been evaluated.…”
Section: Introductionmentioning
confidence: 96%